Carcinoma espinocelular : características clínicas intra-orais e demográficas em uma população do Sul do Brasil e potenciais interações com as células endoteliais linfáticas - Alves, Alessandro Menna (2013)
This dissertation was divided into two distinct works, which can be summarized as follows: Article 1: The oral squamous cell carcinoma (OSCC) is the most prevalent malignance in mouth, being an important public health problem. The aim of this study was to evaluate the clinical and epidemiological profile of the OSCC cases registered in a center of clinical and histopathological diagnosis, located in Southern Brazil. Eight hundred and six individuals with OSCC and its variants were included in this study, over 1959-2012 period. The variables recorded from the files were: age, gender, skin color, tumor location, size and evolution time of the lesions (referred by the patients), as well as, the presence of pain lymph nodes, habits of tobacco and alcohol, and also the profession. OSSC was more frequent in males (76.6%), with the majority of cases distributed between 51 and 70 years old (53.9%). The most prevalent sites were lower lip vermilion [23.3% (20.4; 26.4)], followed by lateral border/ventral surface of the tongue [20.2% (17.5; 23.2)], gingiva/alveolar ridge [18.1% (15.5; 21.0)], and floor of the mouth [14.9% (12.5; 17.5)]. A strong association between outdoor occupation and OSCC in lower lip vermilion was found. The OSCC lesions located in tongue, gingiva/alveolar ridge and floor of the mouth were commonly more painful, bigger than 2 cm, and frequently presenting lymph nodes involvement. Most of the results confirm the data from literature. Mouth self-examination should be recommended and campaigns of prevention and early detection of OSCC should be periodically performed in order to increase people s feelings of personal risk. Article 2: Inside the tumor microenvironment (TM) the neoplastic cells are in dynamic crosstalk with the vascular and lymphatic endothelial cells in order to allow the tumor to growth and metastasize. Hypothesizing that there is a crosstalk between lymphatic endothelial cells and tumor cells from squamous cell carcinoma (SCC) that plays an important role in metastasis, we aimed to identify potential interactions between lymphatic endothelial cells and tumor cells lines from SCCs, through some in vitro assays. Primary adult human dermal lymphatic microvascular endothelial cells (HMVECs) and the human head and neck SCC cell lines like A431, UM-SCC-1, UM-SCC-22A and UM-SCC-22B were cultured in their specific media. UM-SCC cells lines were treated with rhIL-6, being VEGF-C expression checked by Elisa. Baseline IL-6 was evaluated in HMEVCs using the same assay. Also the IL-6 receptor (IL-6R) was analyzed by Western blot in UM-SCC cells. Conditioned media from HMVECs were prepared with different treatments and incubated with SCC A431 cells, in order to verify the MMPs enzymatic activities by gelatin zymography. Our results demonstrated that there are interactions between tumor cells and LECs, since the LECs-CM were able to enhance MMP-2 gelatinolytic activity. Moreover, we showed that LECs secrete IL-6, and different SCC lines have receptors for this cytokine. Therefore, our results indicate some potential interactions between LECs and TCs, being necessary other studies to elucidate the involved signaling pathways